Innovation And Biotechnology Of Coffee Peel Waste Using Different Fermenters As Alternative Feed Animal - Roni Yulianto; Gusna Merina (Journal of Multidisciplinary Science, 2022)
The waste of peel coffee was potential to be used as feed animal because it is rich in nutritional quality for livestock needs. The Purpose of this study consist of: 1) Developing biotechnology and innovation of feed made from coffee peel waste as an alternative feed to support agro-industry, 2) Utilization of appropriate local raw material innovations as quality feed animal to increasing the nutritional value, growth and production of livestock; 3) Reduce the cost of forage substitution feed production using coffee rind as feed animal.Observation and collection of quality coffee peel waste, 2) Preparation and manufacture of fermenters, 3) Processing and manufacturing of fermented coffee peel waste feed additives, 4) Analysis of the nutritional quality of coffee peel waste using several fermenters. The results of the study using mixed coffee peel + local microrganism of the tempeh yeast is very significant and has a high nutrient content, much higher than other fermenters when viewed from dry matter 88.1%, crude protein 27.20%, crude fat 16.90%, Total Digestible Nutrient (TDN) 72.50%, and Crude Fiber decreased by 15.60%. The results of the study using coffee peel waste were alternative to the feed animal to support agro-industry it can be concluded fermenters using mixed coffee peel + local microorganism tempeh yeast have a high content when viewed from dry matter 88.1%, Crude Protein 27.20 %, Crude Fat 16.90%, TDN 72.50%, and Crude Fiber decreased by 15.60%.